ASSESSMENT OF THE KNOWLEDGE AND ATTITUDE TOWARDS CIGARETTE SMOKING AMONG YOUTHS IN OGBIA TOWN; OGBIA LOCAL GOVERNMENT AREA OF BAYELSA STATE - Emerinwe (Ph.D), Obuzor, Mezewo; Nwabueze (Ph.D), Emeodu, Elijah; Dokubo, Ariwera (Journal of Medical Genetics and Clinical Biology, 2024)
This study investigated the assessment of the knowledge and attitude towards cigarette smoking among youths in Ogbia Town; Ogbia Local Government Area of Bayelsa State. The population of the study consisted of three hundred (300) Youths, and one hundred and fifty 150 (50%) were selected as the sample size for the study. The simple random sampling technique and systematic sampling techniques were adopted to select the sample for the study. Three research questions and objectives were used. The instrument used for data collection was a well-structured questionnaire; simple percentage was used to answer the research questions. The results showed that; 95.3% of the respondents knew the negative effect of cigarettes on health; 96.7% of the respondents said smoking should be strictly prohibited in public areas. 96.0% of the respondents indicated that Smoking is a disgusting behavior; 90.0% of the respondents indicated that smoking is hazardous to the health of others, while 19.3% of the respondents did not accept that smoking is a personal freedom. Again, 84.0% of the respondents indicated that peer groups influenced the cigarette smoking habits among youths. In light of the findings of the study, it was therefore recommended that; policies prohibiting the advertisement and use of tobacco in public places be properly enforced by the government, parents, and educational management; and finally that religious leaders should be good role models that will help youths in quitting cigarettes smoking